Assessment of Challenges Encountered by Dutch Oncologists When Patients Ask for Second Opinions - Hillen, Marij A. (JAMA Oncol, 2018)
This analysis of interviews with Dutch oncologists investigates the outcomes of second-opinion requests for physician-patient and physician-colleague relationships.